Orologi ad acqua nell´antichitá greco-romana - Di Pasquale, Giovanni (ENDOXA, 2005)
This paper deals with ancient clepsydrae and water docks in Greece and Rome. While clepsydrae are very oíd time measuring instruments, the difíusion of water docks is strictly connected with the development of the mechanical studies. Ctesibius of Alexandria was the first one to understand the bind links between pneumatical toys and the water docks. Really interesting is the description of the Archimedes water dock, a complex device whose mechanical engine is just similar to the Vitruviu's odometer.